General Characteristics of Service of Procedural Documents in Polish Civil Proceedings Compared to Selected European Countries - Emil Kowalik (Review of European and Comparative Law)
The institution of service by a court enforcement officer has had a significant impact on the regularity of the service of court letters. The provisions introduced put an end to the so-called fiction of service on individuals, which meant that after two attempts at service, the court could assume that the document had been effectively served. It was recognized that this too often led to prejudice to the rights of defendants, in particular those who had not lived at the addresses indicated by the plaintiffs for a long time - often, due to the correct (fictitious) service of payment orders, they were obliged to pay the amounts resulting from final court decisions. Unfortunately, under the previous legislation, there were cases of claimants giving unverified or even false information. The legislator obligatorily introduced into the Polish legal order, in Article 1391 of the Code of Civil Procedure, the service of letters through a court bailiff in the event that a statement of claim or any other writ of summons that gives rise to the need to defend the rights of the defendant has not been effectively served on the defendant in accordance with 131–139 of the Code of Civil Procedure. Thus, the legislator, contrary to the principle of routine service, imposed the resulting obligations not on the procedural authority, but on the initiator of the proceedings in the case. This study aims to present the institution of the bailiff in Polish civil proceedings and discuss its advantages and disadvantages. It is particularly relevant in light of the changes introduced by the amendment of the CPC of 9 March 2023, effective from 1 July 2023, which are designed to improve this type of service.